Magnesiovesuvianite, Ca19Mg(Al,Mg)12Si18O69(OH)9, a new vesuvianite-group mineral - Panikorovskii,T.L.; Shilovskikh,V.V.; Avdontseva,E.Yu.; Zolotarev,A.A.; Karpenko,V.Yu.; Mazur,A.S.; Yakovenchuk,V.N.; Bazai,A.V.; Krivovichev,S.V.; Pekov,I.V. (Journal of Geosciences, 2017)
Magnesiovesuvianite (IMA 2015-104), ideally Ca19Mg(Al,Mg)12 Si18O69(OH)9, a new vesuvianite-group member, was found in an old museum specimen labelled as vesuvianite from the Tuydo combe, near Lojane, Republic of Macedonia. It occurs as radiating aggregates up to 2 cm across consisting of acicular tetragonal crystals (up to 7 mm long and 5-40 μm thick) with distinct fibre-optic effect. Associated minerals are calcite, grossular-andradite and clinochlore. Single crystals of magnesiovesuvianite are transparent, light pink with a silky lustre. Dominant crystal forms are {100}, {110}, {101} and {001}. The Mohs’ hardness is 6. The measured and calculated densities are 3.30(3) and 3.35 g/cm3, respectively. Mineral is optically uniaxial, negative, ω = 1.725(2), ε = 1.721(2). The chemical composition (wt. % electron-microprobe data) is: SiO2 36.73, Al2O3 20.21, CaO 36.50, MgO 1.80, MnO 0.18, FeO 0.04, Na2O 0.01, H2O 3.10, total 98.37. The empirical formula based on 19 (Ca + Na) apfu is: (Ca18.99Na0.01)Σ19.00 (Mg0.60Al0.40)Σ1.00
Keywords: magnesiovesuvianite; new mineral; light conductor; cation ordering; Lojane; Republic of Macedonia